Restorative Narrative of Covid-19 Patients as Health Campaign Message: A Content Analysis of Youtube Videos - Pramana, Pinandito Dhirotsaha; Utari, Prahastiwi; Naini, Albert Muhammad Isrun (Technium Social Sciences Journal, 2020)
This study discussed the restorative narrative message of the first-three recovered Covid-19 patients as well as the resulted public response related to the public health campaign about the Covid-19 pandemic in Indonesia. The context of this research was the benefits of policy-making by the Indonesian government on the introduction of the first-three patients of Covid-19 to the public through a press conference. The research was conducted with qualitative and quantitative content analysis method. Qualitative analysis was to analyze restorative narrative messages carried out on the stories of the three patients on two YouTube videos taken from the accounts @tvOneNews and @CNNIndonesia. The narrative elaboration was explained according to the narrative functions delivered by Sharf & Vanderford and Sharf, Harter, Yamasaki & Haidet. Quantitative analysis was then carried out to find out the ten most common phrases of 7,381 comments on the sample videos to know the public response on restorative messages. The results of the narrative analysis showed that the stories told by three cured Covid-19 patients have meet the restorative narrative criteria and produced positive emotional responses from the public, so that the restorative narrative could be useful for public health campaigns.